Knowledge, attitudes and adherence to treatment in individuals with hypertension and diabetes mellitus - Rosso Mazzuchello, Francielle; Tuon, Lisiane; Simões, Priscyla Waleska; Mazon, Josete; Santina Dagostin, Valdemira; Damiani Tomasi, Cristiane; Hoepers, Neiva; Vieira Bez Birolo, Ioná; Vieira Bez Birolo, Ioná; Bisognin Ceretta, Luciane; Bisognin Ceretta, Luciane (O Mundo da Saúde, 2016)
Chronic Noncommunicable Diseases (NCD) constitute a major health problem in Brazil and corresponds to about 70% of the causes of death. The most common are systemic arterial hypertension and diabetes mellitus, which require the patients to be more closely controlled for its treatment and management². This study aimed to analyze the knowledge, attitudes and adherence to the treatment of individuals with arterial hypertension and associated type 2 diabetes mellitus, accompanied by a Family Health team. This was a cross-sectional, descriptive and prospective quantitative approach. The population consisted of patients diagnosed with hypertension and type 2 diabetes mellitus, enrolled in the HIPERDIA program. Data were collected from August to November of 2014 through the Diabetes Knowledge Scale Questionnaire (DKN-A); Diabetes Attitudes Questionnaire (ATT-19) and Martín-Bayarre-Grade (MBG). 102 individuals were interviewed, the majority of whom were women, married, white, with low schooling, and with a median age of 68.5 years. Everyone was on medication and most of them did not practice any kind of physical activity. An unsatisfactory result was found in relation to the knowledge about the disease, negative attitude regarding the management of the disease, and partial adherence to the treatment. It is thus considered that individuals with hypertension and diabetes mellitus did not modify their attitudes regarding the adoption of healthy life habits for the more adequate coping of the disease.